Anomalous thermal expansion behavior in Er1-xCaxMnO3. Issue 5 (1st April 2020) - Jiao, Yajie; Wang, Hui; Yang, Mengjie; Chao, Mingju; Tang, Xinbo; Chen, Rui; Zhu, Yanwen; Guo, Juan; Gao, Qilong; Liang, Erjun
Abstract: Perovskite Er1- x Ca x MnO3 ( x  = 0, 0.1, 0.2, 0.25, 0.3, 0.4, 0.5) was synthesized using a solid-state method. Thermal expansion behavior was tested using a thermal dilatometer and high-temperature X-ray diffraction (XRD). The experimental results indicated the doping contents of Ca ( x ) in the Er1- x Ca x MnO3 have a dramatic effect on their thermal expansion behavior. The samples of Er1- x Ca x MnO3 ( x  = 0.1, 0.2 and 0.25) exhibit positive thermal expansion (PTE) characteristics while Er0.7 Ca0.3 MnO3 ( x  = 0.3) exhibits a negative thermal expansion (NTE) property with a thermal expansion coefficient of −3.1 × 10 −6  K − 1 in room temperature (RT) −750 K. In addition, Er0.6 Ca0.4 MnO3 ( x  = 0.4) exhibits NTE properties only at RT–500 K, and Er0.5 Ca0.5 MnO3 ( x  = 0.5) exhibits PTE properties at RT–750 K. The thermal shrinkage mechanism is the Jahn–Teller effect of the Mn 3+ ions and the double exchange of Mn 3+ –O–Mn 4+ in Er0.7 Ca0.3 MnO3 . This phenomenon causes Mn–O octahedral distortion and oxygen vacancy, causing Er0.7 Ca0.3 MnO3 to become anisotropic. This feature results in the elastic deformation of Er0.7 Ca0.3 MnO3 during heating, which consumes the void and displays NTE at macro level.